The Synergistic Role of Irreversible Electroporation and Chemotherapy for Locally Advanced Pancreatic Cancer - Gyftopoulos, Argyrios; Ziogas, Ioannis A.; Barbas, Andrew S.; Moris, Dimitrios (Frontiers in Oncology, 2022)
Irreversible electroporation (IRE) is a local ablative technique used to treat locally advanced pancreatic cancer (LAPC) in conjunction with chemotherapy. The combination of IRE and chemotherapy has showed increased overall survival when compared to chemotherapy alone, pointing towards a possible facilitating effect of IRE on chemotherapeutic drug action and delivery. The current review aims to present current chemotherapeutic regimens against LAPC and their co-implementation with IRE, with an emphasis on possible molecular augmentative mechanisms of drug delivery and action. Moreover, the potentiating mechanism of IRE on immunotherapy, M1 oncolytic virus and dendritic cell (DC)-based treatments is briefly explored. Investigating the synergistic effect of IRE on currently established treatment regimens as well as newer ones, may provide exciting new directions for future studies seeking to improve current LAPC treatment algorithms.